en - Pongmasangka, Nico Linggi; Malik, Anis Rohmana; Erwandi, Dadan (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Psychosocial risk factors can be stressors that have an impact on increasing work stress cases in a workplace. These risk factors cause various kinds of problems in workers such as occupational diseases and work accidents. One of the psychosocial measurement models in the workplace is the Copenhagen Psychosocial Questionnaire (COPSOQ) II. The sampling technique in this study used the Exhaustive Sampling Technique which was carried out on October 25 - 28, 2021 at PT. XYZ the number of samples is 34 workers. The results of this study found that the percentages were almost balanced between the good and bad categories, namely "good" psychosocial conditions 41.2% (14 people) and "bad” by 58.8% (20 people). The psychosocial aspect that has the highest percentage in the "bad" category is the Health and Welfare Aspect with a percentage of 76.50% (26 people). In the results of the bivariate test, it was found that there was a significant relationship between psychosocial aspects and emotional risk factors experienced by employees at PT. XYZ